2007
DOI: 10.1007/s10336-007-0186-5
|View full text |Cite
|
Sign up to set email alerts
|

Avian senescence: underlying mechanisms

Abstract: Candidate mechanisms for physiological aging include free radical production and resulting oxidative damage, progressive erosion of telomeres and cellular senescence, age-dependent trade-offs in hormone signaling pathways, and immunosenescence, leading to an increased risk of infection, autoimmune disease, and cancer. These mechanisms are inter-related, not mutually exclusive, and probably all contribute to the aging phenotype. To date, most studies on mechanisms of aging are based on cell culture or lab anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 181 publications
(179 reference statements)
2
37
0
Order By: Relevance
“…The decline in the PHA response by aged Cory's Shearwaters is consistent with results from recent studies indicating that immunosenescence may be common in both short and long-lived bird species (Haussmann et al 2005;Vleck et al 2007). It also suggests that Old birds in our study had reached an age where senescence effects might be apparent (see also Mougin 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The decline in the PHA response by aged Cory's Shearwaters is consistent with results from recent studies indicating that immunosenescence may be common in both short and long-lived bird species (Haussmann et al 2005;Vleck et al 2007). It also suggests that Old birds in our study had reached an age where senescence effects might be apparent (see also Mougin 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, measuring other aspects of individual state and performance may contribute to a better understanding of the mechanisms of aging, and hence of the biology of senescence. Although there has been recent research focusing on hormonal, physiological and cellular parameters (Haussmann et al 2005;Vleck et al 2007), surprisingly few studies have explored the effects of aging of wild animals on traits such as foraging behaviour and efficiency (but see Catry et al 2006;MacNulty et al 2009;Lecomte et al 2010). Such traits are highly relevant because they influence the rate of resource acquisition, and hence have major implications for fitness correlates that include reproductive output and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Studies describing changes in oxidative stress throughout life are abundant in mammalian literature (Oztürk and Gümüşlü 2004;Gil et al 2006). In contrast, avian reports are mostly limited to the early stages of life because data on aged birds are scarce (e.g., Alonso-Alvarez et al 2006;Torres and Velando 2007;Vleck et al 2007). Furthermore, as far as we know, no avian study describes the change in any marker of oxidative damage across the full age range (i.e., from youth to old age; see also the review by Vleck et al [2007]).…”
Section: Introductionmentioning
confidence: 99%
“…Birds constitute an attractive group of organisms for comparative studies of senescence, first because they are relatively long-lived for their body sizes compared to mammals due to their slower life histories (Jones et al 2008), and second because data on wild birds have been collected in a wide range of avian species (Vleck et al 2007). Several studies of short-lived birds have recently shown evidence for survival senescence (e.g., Fox et al 2006, Keller et al 2008.…”
Section: Discussionmentioning
confidence: 99%